From Taqlid to Inclusion: The Transformation of Islamic Education During the Islamic Renewal in Egypt - Muhammad Irfan; Astuti Purwasari (Program Pascasarjana UIN Sumatera Utara, 2025)
The transformation of Islamic educational thought during the Islamic Renewal (tajdid) period in Egypt (19th to early 20th century) was an intellectual response to Western modernity, colonialism, and the scholarly stagnation plaguing the Islamic world. This research focuses on the shift from a taqlid paradigm towards an inclusive approach. It employs a qualitative approach with historical-descriptive analysis of primary and secondary texts and documents to trace how reformist thinkers, such as Muhammad Abduh and Rashid Rida, criticized intellectual stagnation and called for a more contextual and adaptive reinterpretation of Islamic teachings. The analysis in this study explains that the renewal movement not only reformed the curriculum of Islamic education-by integrating religious sciences and modern science-but also introduced values of inclusivity. These transformative efforts included the diversification of disciplines taught, the introduction of more dialogical and critical teaching methods, and the integration of modern values such as rationality, tolerance, gender equality, acceptance of intellectual plurality, and interfaith dialogue. Nevertheless, this process was not without resistance and internal debates. The shift towards inclusivity in Egyptian Islamic education, marked by efforts to open up to new ideas and involve diverse perspectives, represents a reconstruction of Islamic epistemology relevant to modernity, and simultaneously a significant evolution in facing constantly changing social and intellectual dynamics. This article concludes that the legacy of Islamic educational thought during the renewal period in Egypt offers a transformative model for the development of contemporary Islamic education that balances tradition and progress. This transformation is not just about curriculum changes, but also about reconceptualizing the role of Islamic education in shaping a more progressive and open society.